Analisis Dinamika Masyarakat Dalam Berdemokrasi di Era Pra- Reformasi dan Pasca-Reformasi Dalam Pemilihan Umum - Zahratu, Nazwa Salsabila; C, Chatrine; Fiandie, Ursula Jacqueline; Triadi, Irwan (Media Hukum Indonesia (MHI), 2024)
In 1945, Indonesia proclaimed its independence from colonial rule. In the following decades the Indonesian nation has experienced significant changes, especially in the government system. This article discusses the analysis of elections in Indonesia, which are influenced by the development of a democratic government system. The method used is normative juridical, where legal research is carried out by examining library materials or secondary data. This research uses a literature study as a data collection method. The research concludes that the implementation of a democratic system cannot be separated from the implementation of constitutional democracy. Democracy is chosen over other systems because it is considered the best. Making people aware of their rights and obligations, and democracy must be fully carried out by "Policy Makers" as the power to regulate and/or run the government in accordance with the law.